Grammar for people who hate grammar [filem jalur] (Mount Kisco, NY : Guidance Ass., 1978)
Contents: 1. Language basic : punctuation -- 2. Language basics : verbs -- 3. Language basics : nouns -- 4. Language basics : adjectives and nouns -- 5. Language basics : pronouns